2006
DOI: 10.1063/1.2336780
|View full text |Cite
|
Sign up to set email alerts
|

The molecular origins of nonlinear response in solute energy relaxation: The example of high-energy rotational relaxation

Abstract: A key step in solution-phase chemical reactions is often the removal of excess internal energy from the product. Yet, the way one typically studies this process is to follow the relaxation of a solute that has been excited into some distribution of excited states quite different from that produced by any reaction of interest. That the effects of these different excitations can frequently be ignored is a consequence of the near universality of linear-response behavior, the idea that relaxation dynamics is deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
103
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(116 citation statements)
references
References 56 publications
13
103
0
Order By: Relevance
“…The agreement is better at shorter times. The dynamic linear-response approximation, C g (t), describes the ∼150 fs inertial solvation dynamics quite well, consistent with previous reports for other models 9,14,15 and attributed to the similarity between the nonequilibrium inertial motion and the equilibrium dynamics in the ground state. An intermediate time scale in the solvation dynamics corresponding to diffusive solvent reorientation, is also reasonably represented in the linear response results, though its amplitude is not.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The agreement is better at shorter times. The dynamic linear-response approximation, C g (t), describes the ∼150 fs inertial solvation dynamics quite well, consistent with previous reports for other models 9,14,15 and attributed to the similarity between the nonequilibrium inertial motion and the equilibrium dynamics in the ground state. An intermediate time scale in the solvation dynamics corresponding to diffusive solvent reorientation, is also reasonably represented in the linear response results, though its amplitude is not.…”
Section: Discussionsupporting
confidence: 74%
“…linear-response behavior. 8,9 By a detailed examination of the trajectories, it was possible to identify a distinct transition in dynamics when the CN rotor pushed an argon atom out of the first solvation shell. The dynamics prior to this event are well described by linear response while those following it are not.…”
Section: Introductionmentioning
confidence: 99%
“…͑8͔͒, which assumes that the excited-state dynamics are not far removed from the ground-state dynamics. 8,13,18 This implies that the approximation may have a wider validity for complex systems-e.g., timedependent fluorescence in nanoconfined solvents where the ground-and excited-state statistics can be dramatically different due to the dependence of the solute position on the electronic state-than indicated by the traditional linearresponse approximation.…”
Section: ͑21͒mentioning
confidence: 99%
“…[8][9][10][11][12][13] Such cases are sometimes considered to represent a breakdown of the linear-response approximation, though, for example, Tao and Stratt argue, but do not prove, that a stronger condition is more appropriate-one based on whether the energy gap exhibits Gaussian statistics, since "linear-response predictions are obeyed exactly if the liquid fluctuations obey Gaussian statistics." 13 Skaf and Ladanyi found that the linear-response approximation can be unsatisfactory even when the ground-and excited-state correlation functions are the same. 14 Since the derivation of the excitedstate correlation function from Eq.…”
mentioning
confidence: 99%
“…The difference between equilibrium and non-equilibrium rotational relaxation reflects, in part, the difference between the equilibrium structure of the solutesolvent complex. 468,483 The insight gained from studying a simple diatomic solute has been useful for understanding the rotational behavior of large dye molecules. 484 Let us now consider the reorientation dynamics at the liquid/liquid interface.…”
mentioning
confidence: 99%